Une expérience de recherche documentaire sur Internet en classe de langue : propositions de modélisation didactique - Alain Verreman (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Groups of secondary school students conducted guided searches on Internet sites in German. About 120 students were involved in the project. The experiment described in this paper is first used as the basis for a study on the pedagogical relevance of Internet-based research by pupils in foreign languages. We argue that this type of activity is worthwhile only insofar as it promotes the learning process. We present some conclusions on the pitfalls that have to be avoided, on the principles that have to be upheld, and on the new prospects which this medium opens up, in the fields of "active teaching methods", of learner autonomy and of oral and written target-language production. Secondly, we scrutinize the procedure as part of a thorough didactic study, bearing in mind criteria such as relevance, coherence, variation and differentiation. Then we relate the results to studies which have already been published on the subject in France and in Germany. Finally we offer a framework of models showing that our procedure partakes both of a cultural model and of a model sometimes known as the model "of the complex task", and we define these in terms of their dominant characters, the principles that underpin them and their pedagogical objectives.